The Exploring Employment Competencies among Private Undergraduate Students: A Factor Analysis in Sichuan Province - Wu , Xuanlin; Chutimant , Poramatdha (Journal of Roi Kaensarn Academi, 2024)
This study examines employment abilities among private undergraduate students in Sichuan Province. This study aims to evaluate the present condition of students' job abilities, identify significant influencing variables, and gather insights from students, educators, and employers in the business sector. At 18 private universities, questionnaires were customized to focus on four variables: professional self-development, interpersonal communication ability, practice-oriented professional competence, and integration of professional knowledge as primary research elements. The data collection included online questionnaires and on-campus interviews, followed by comprehensive data analysis to thoroughly assess student performance in various job competency areas. Research findings indicate that private undergraduate students in Sichuan Province often exhibit certain traits related to occupational abilities. Factor analysis reveals many significant components, including "Core Professional Skill Cultivation" and "Comprehensive Quality Enhancement," which are essential in fostering students' job skills. This enables private colleges to get critical insights for refining talent development methods to enhance students' employability and realize their full potential as job candidates.